PENDAMPINGAN BRANDING PACKAGING DAN MANAJEMEN MEREK UMKM MADU KELULUT DESA KUALA SEMPANG - Muhammad Mu’azamsyah; Marsudi, Marsudi; Dewi Artha Hutasoit; Essy Viona Sihombing; Muhammad Azmi; Prayoga Dwi Guna (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Kelulut Madu UMKM was established in 2019, located in Kuala Sempang Village, Sri Kuala Lobam District, Bintan Regency, Riau Islands Province. The problems faced by Kelulut Pak Asril Madu UMKM, Pak Asril Village, Kuala Sempang include firstly, Kelulut Pak Asril Madu UMKM, Kuala Sempang. There is no brand logo for Kelulut Pak Asril Madu UMKM, secondly, they are experiencing difficulties in ordering packaging because the product often experiences damage during delivery. So, group 3 of KKN-P2EM STIE DEVELOPMENT TANJUNGPINANG 2023-2024 created a program that focuses on product packaging and brand management which aims to branding existing brands into brands that have selling value, assisting in Branding Packaging (product packaging) from creating logos and a more attractive brand so that it attracts consumers' buying interest, as well as giving a banner to MSME Madu Kelulut Pak Asril, Kuala Sempang Village, then sharing and explaining that knowledge of brand management is very necessary.